Mordenite with ultra-small particle size as well as preparation method and application of mordenite

By using a combination-oriented method of seed crystal and template agent in the preparation of mordenite, ultra-small particle size mordenite with multi-stage self-assembled nanoparticles was synthesized, which solved the problem of insufficient diffusion performance of nanomaterials in the prior art, and achieved efficient conversion of fused ring aromatic hydrocarbons and production of light aromatic hydrocarbons.

CN119898788APending Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311402534.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the prior art, block-shaped agglomerated nanomaterials such as strips, discs and spherical shapes have single exposed crystal surfaces and insufficient exposure of effective orifices, resulting in a diffusion performance that is not suitable for treating heavy heavy aromatic hydrocarbons, especially dense ring aromatic hydrocarbons.

Method used

By utilizing the combination-oriented method of seed crystal and template agent, a mordenite with multi-stage self-assembled nanoparticles is synthesized by secondary crystallization to ensure ultra-small particle size and sufficient orifice exposure.

Benefits of technology

It realizes efficient diffusion of fused-cyclic aromatic hydrocarbon raw material molecules, improves reactive activity and selectivity, and is suitable for the BTX reaction process of fused-cyclic aromatic hydrocarbon conversion to produce light aromatic hydrocarbons.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898788A_ABST
    Figure CN119898788A_ABST
Patent Text Reader

Abstract

The invention discloses mordenite with an ultra-small particle size and a preparation method and application thereof. The mordenite comprises nano particles with the diameter of 5-100 nm, the mesoporous volume of the mordenite is 0.1-0.6 cm < 3 > / g, the average mesoporous aperture of the mordenite is 5-80 nm, and the amount of B acid on the outer surface of the mordenite accounts for 5%-80% of the total amount of B acid. According to the present invention, the problem is well solved by using the full exposure degree of the ultrafine particle size to the effective orifice, and the catalyst is used for the light aromatic hydrocarbon production reaction through the polycyclic aromatic hydrocarbon conversion, has advantages of high reaction activity and high selectivity, and can be used in the industrial production of the aromatic hydrocarbon conversion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of mordenite, and in particular relates to mordenite with ultra-small particle size and a preparation method and application thereof. Background Art

[0002] Molecular sieve nanoparticles often refer to molecular sieves with a particle size less than 100nm. Due to the extremely small crystal size, molecular sieve nanoparticles often have a higher external specific surface area under the condition of ensuring sufficient micropore channels. Due to the non-uniform distribution of active sites on the inner and outer surfaces of molecular sieves, molecular sieve nanoparticles fully exposed on the outer surface often have more effective catalytic active sites, making molecular sieve nanoparticles have higher reaction activity, especially for macromolecular conversion. Moreover, molecular sieve nanoparticles have a larger external specific surface area and external pore volume, while increasing the diffusion performance of reactants and products, the carbon capacity is also improved to a certain extent compared with traditional microporous molecular sieves, so it can effectively reduce the carbon deposition rate inside and outside the catalyst channel, improve reaction stability and the service life of the catalyst. Zhang Kun et al. (CN102718231A) used hexadecyltrimethyl p-toluenesulfonic acid as a structure-directing agent to synthesize small-grained layered nano-mordenite with a sheet thickness of about 50nm. Shen Wenjie et al. (CN107963637A) used specially designed hexadecyl N-dimethylethyl-N, N-dimethylammonium bromide as a template to synthesize a sheet-like mordenite zeolite oriented with the c-axis. Qi Xiaolan et al. (CN102190316A) used an organic amine structure directing agent method to synthesize a mordenite molecular sieve with a microporous-mesoporous composite pore structure under hydrothermal conditions. Xing Shujian et al. (CN1847046A) added seed crystals, used sodium chloride or sodium sulfate metal salts as additives, aged at 100°C, and then hydrothermally crystallized at 130-150°C to obtain spherical aggregates of mordenite with an average size of 42-90nm. Hao Qingqing et al. (CN106517239A) used hexamethyleneimine as a template to synthesize a swellable layered mordenite molecular sieve. The sheet-like molecular sieves synthesized by many scholars have better catalytic performance than traditional mordenite. It can be seen that the catalytic performance of this type of thin-sheet molecular sieve is far superior to the block-shaped MOR molecular sieve synthesized by the traditional method, and has broad application prospects in the field of catalysis. Kong Dejin et al. (CN107754847B) disclosed a nano-aggregated sheet-shaped mordenite catalyst. The synthesized mordenite is spontaneously aggregated by short columnar nanocrystals with three-dimensional dimensions between 5 and 500 nm, has a sheet-like morphology, has excellent reaction performance in high-space-speed aromatic conversion reactions, and effectively inhibits the occurrence of side reactions such as aromatic polymerization and cracking. Tong Weiyi et al. disclosed mordenite with chain-like nano self-assembled aggregate morphology in CN108499595B and CN108465478B, respectively. The thickness of a single sheet-shaped crystal is between 1 and 500 nm and 6.5 and 189 nm, respectively, and has good performance in aromatic transalkylation reactions. Therefore, mordenite with a lamellar morphology plays an important role in the conversion process of aromatics.

[0003] The present invention discloses a method of using a combination of seed crystals and template agents to guide, and adopts a secondary crystallization method to synthesize a multi-level self-assembled nanoparticle mordenite and a preparation method thereof, which is particularly suitable for the reaction process of light-weight conversion of inferior aromatic hydrocarbons, especially condensed aromatic hydrocarbons, to increase the production of BTX. The overall self-assembled particles have a micron size, which is convenient for filtering and washing of molecular sieves. Summary of the invention

[0004] The technical problem to be solved by the present invention is that the existing block-shaped agglomerated nanomaterials in the prior art, such as strips, disks and spheres, have defects in practical applications, such as insufficient exposure of effective pores, slow diffusion of raw material molecules and poor diffusion channels due to the single exposed crystal face, resulting in the diffusion performance being unsuitable for processing heavy heavy aromatic hydrocarbons, especially condensed ring aromatic hydrocarbons such as naphthalene series, indenes and other raw materials. In order to solve the above problems, the present invention discloses a mordenite catalyst with ultra-small particle size and its preparation method and application, wherein the above problems are better solved by utilizing the sufficient exposure of the effective pores by the ultra-fine particle size, and the catalyst is used for the conversion of condensed ring aromatic hydrocarbons to produce light aromatic hydrocarbons, and has the advantages of high reaction activity and selectivity, and can be used in the industrial production of aromatic hydrocarbon conversion.

[0005] On one hand, the present invention provides a mordenite with ultra-small particle size, wherein the mordenite comprises nanoparticles with a diameter of 5 to 100 nm, and the amount of Br acid on the outer surface of the mordenite accounts for 5% to 80% of the total Br acid amount.

[0006] The mesopore volume of the mordenite is 0.1-0.6 cm 3 / g; preferably, the average mesopore diameter of the mordenite is 5-80nm.

[0007] The specific surface area of ​​the mordenite is 320 to 865 m 2 / g, external specific surface area is 70~610m 2 / g.

[0008] The amount of B acid on the outer surface of the mordenite is 30-250 μmol / g.

[0009] The second object of the present invention is to provide a method for preparing mordenite with ultra-small particle size, the preparation method comprising:

[0010] (1) treating a seed crystal precursor with alkali to obtain a solid seed crystal;

[0011] (2) mixing a silicon source, an aluminum source, an alkali, water and the solid seed crystal to obtain a mixture, adding the mixture into a crystallization kettle, and stirring;

[0012] (3) adding a structure directing agent into the crystallization kettle and performing a crystallization treatment to obtain a crystallized product;

[0013] (4) The mordenite is obtained through post-treatment.

[0014] In step (1), the seed crystal precursor and the solid seed crystal are each independently a silicon-aluminum porous material having a MOR and / or FAU and / or BEA and / or MWW and / or FER topological structure.

[0015] In step (2), the silicon source is selected from one or more of silicon oxide, water glass, silica sol, ethyl silicate, sodium silicate, silica gel, and white carbon black.

[0016] In step (2), the aluminum source is selected from one or more of boehmite, pseudo-boehmite, aluminum hydroxide, sodium aluminate, aluminum sulfate, aluminum nitrate, and aluminum isopropoxide.

[0017] The alkali in step (2) is at least one selected from sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, and potassium bicarbonate.

[0018] In step (2), the molar ratio of the silicon source to the aluminum source is 5 to 60, the molar ratio of the alkali to the silicon source is 0.005 to 0.5, and the molar ratio of the water to the silicon source is 5 to 100, wherein the molar amount of the silicon source is calculated as SiO2, the molar amount of the aluminum source is calculated as Al2O3, and the molar amount of the alkali is calculated as the molar amount of the metal oxide therein.

[0019] In step (2), based on 100 wt % of the mixture, the content of the solid seed crystals is 0.01 to 50 wt %.

[0020] In step (3), the structure directing agent is selected from one or more of linear or branched alkylamines, cyclic alkylamines, tetraalkylammonium halides, tetraalkylammonium hydroxides, ammonia water, and alkyl diammonium bromides.

[0021] Preferably, in step (3), the structure directing agent is selected from one or more of ethylamine, hexylamine, ethylenediamine, hexyldiamine, tetraethylammonium bromide, tetraethylammonium hydroxide, tetramethylammonium bromide, tetramethylammonium hydroxide, tetrapropylammonium bromide, tetrapropylammonium hydroxide, tetrabutylammonium bromide, tetrabutylammonium hydroxide, ammonia water, hexamethyleneimine, cyclohexylamine, and hexamethylammonium bromide (HMBr2).

[0022] More preferably, the molar ratio of the structure directing agent in step (3) to the silicon source in step (2) is 0.0005 to 1, preferably 0.001 to 0.5.

[0023] In step (3), the crystallization treatment includes: heating to a crystallization temperature of 120-220° C., and crystallizing at this temperature for 0.5-60 hours; preferably, heating to a crystallization temperature of 150-200° C., and crystallizing at this temperature for 1-48 hours.

[0024] The third object of the present invention is to provide a zeolite catalyst, which includes mordenite, a binder and a metal component, wherein the mordenite is selected from the mordenite described in the first object of the present invention or the mordenite obtained by the preparation method described in the second object of the present invention.

[0025] The binder is selected from at least one of alumina, aluminum sol, silica sol and pseudo-boehmite.

[0026] The metal component is selected from at least one or more of platinum, molybdenum, bismuth, tin, cadmium, cobalt, nickel, rhenium, palladium, gallium, ruthenium and lanthanum.

[0027] In 100 wt% of the zeolite catalyst, the mordenite accounts for 3-98 wt%, the binder accounts for 2-90%, and the metal component accounts for 0.0001-20 wt%.

[0028] The fourth object of the present invention is to provide a method for preparing a zeolite catalyst, preferably for preparing the zeolite catalyst described in the third object of the present invention, wherein the preparation method comprises: first mixing the mordenite with the binder to obtain a matrix, then loading the metal component thereon, and finally obtaining the zeolite catalyst through post-treatment.

[0029] A fifth object of the present invention is to provide the use of the mordenite and the zeolite catalyst in the conversion of condensed aromatic hydrocarbons to produce light aromatic hydrocarbons.

[0030] The sixth object of the present invention is to provide a method for converting polycyclic aromatic hydrocarbons into light aromatic hydrocarbons, comprising: reacting polycyclic aromatic hydrocarbons with hydrogen in the presence of the mordenite and the zeolite catalyst.

[0031] The endpoints and any values ​​of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, the endpoint values ​​of each scope, the endpoint values ​​of each scope and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) The mordenite of the present invention has an ultra-small nanoparticle size, which exposes the crystal surface and effective pores more fully. It is beneficial to the diffusion of condensed aromatic hydrocarbon raw material molecules and shortens the diffusion distance;

[0034] (2) The higher ratio of the external surface acid content to the total acid content reflects the enhancement of acid accessibility, which helps the polycyclic aromatic hydrocarbon raw material molecules to contact with the acidic sites and undergo conversion, and is suitable for the reaction process of increasing the production of BTX by converting inferior aromatic hydrocarbons, especially polycyclic aromatic hydrocarbons, to lighten the weight. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The SEM picture of the mordenite obtained in Example 1 is shown. DETAILED DESCRIPTION

[0036] The following detailed description of the present invention will make the features and advantages of the present invention more clear and explicit.

[0037] One of the purposes of the present invention is to provide a mordenite with an ultra-small particle size, wherein the mordenite comprises nanoparticles with a diameter of 5 to 100 nm (for example, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm), and the amount of B acid on the outer surface of the mordenite accounts for 5%-80% of the total B acid amount (for example, 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70% or 80%).

[0038] Among them, the higher ratio of the external surface acid content to the total acid content of the mordenite of the present invention reflects the enhancement of acid accessibility. When used, it helps the molecules of polycyclic aromatic hydrocarbons to contact and transform with the acidic sites, and is suitable for the reaction process of light-weight transformation of inferior aromatic hydrocarbons, especially polycyclic aromatic hydrocarbons, to increase the production of BTX.

[0039] In a preferred embodiment, the mesopore volume of the mordenite is 0.1-0.6 cm 3 / g, for example 0.1cm 3 / g, 0.2cm 3 / g, 0.3cm 3 / g, 0.4cm 3 / g, 0.5cm 3 / g or 0.6cm 3 / g.

[0040] In a further preferred embodiment, according to BJH calculation of N2 adsorption and desorption experiments, the average mesopore diameter of the mordenite is 5-80 nm, for example, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm or 80 nm.

[0041] Among them, the smaller the grains, the smaller the intercrystalline pores.

[0042] In a preferred embodiment, the specific surface area of ​​the mordenite is 320 to 865 m 2 / g, external specific surface area is 70~610m 2 / g.

[0043] For example, the specific surface area of ​​the mordenite is 320 m 2 / g, 350m 2 / g, 450m 2 / g, 550m 2 / g, 650m 2 / g, 750m 2 / g, 850m 2 / g or 865m 2 / g, external specific surface area is 70m 2 / g、100m 2 / g, 200m 2 / g、300m 2 / g, 400m 2 / g、500m 2 / g、600m 2 / g or 610m 2 / g.

[0044] In a preferred embodiment, the amount of B acid on the outer surface of the mordenite is 30-250 μmol / g, for example, 30 μmol / g, 50 μmol / g, 100 μmol / g, 150 μmol / g, 200 μmol / g or 250 μmol / g.

[0045] The second object of the present invention is to provide a method for preparing mordenite with ultra-small particle size, preferably for preparing the mordenite described in one of the objects of the present invention, the preparation method comprising:

[0046] (1) treating a seed crystal precursor with alkali to obtain a solid seed crystal;

[0047] (2) mixing a silicon source, an aluminum source, an alkali, water and the solid seed crystal to obtain a mixture, adding the mixture into a crystallization kettle, and stirring;

[0048] (3) adding a structure directing agent into the crystallization kettle and performing a crystallization treatment to obtain a crystallized product;

[0049] (4) The mordenite is obtained through post-treatment.

[0050] In a preferred embodiment, in step (1), the seed crystal precursor and the solid seed crystal are each independently a silicon-aluminum porous material having a MOR and / or FAU and / or BEA and / or MWW and / or FER topological structure.

[0051] In a further preferred embodiment, in step (1), the micropore volume of the solid seed crystal is 0.01-0.25 cm 3 / g (for example, 0.01 cm 3 / g, 0.05cm 3 / g, 0.1cm 3 / g, 0.15cm 3 / g, 0.2cm 3 / g or 0.25cm 3 / g), wherein the micropores refer to pores with a pore diameter less than 2 nm.

[0052] In a preferred embodiment, the alkali treatment in step (1) is carried out using an alkali solution, and the concentration of the alkali solution is preferably 0.05-5M (preferably 0.1-1M), for example, 0.05M, 0.1M, 0.2M, 0.5M, 0.8M, 1M, 2M, 3M, 4M or 5M.

[0053] In a further preferred embodiment, the alkali used in the alkali treatment in step (1) is selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate and potassium bicarbonate.

[0054] In a further preferred embodiment, the alkali treatment in step (1) is carried out at 35-100°C, preferably 40-95°C, for example 35°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C.

[0055] In a preferred embodiment, the alkali treatment in step (1) is followed by filtration and washing, preferably washing with water.

[0056] In a preferred embodiment, in step (2), the silicon source is selected from one or more of silicon oxide, water glass, silica sol, ethyl silicate, sodium silicate, silica gel, and white carbon black.

[0057] In a preferred embodiment, in step (2), the aluminum source is selected from one or more of boehmite, pseudo-boehmite, aluminum hydroxide, sodium aluminate, aluminum sulfate, aluminum nitrate, and aluminum isopropoxide.

[0058] In a preferred embodiment, the base in step (2) is selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate and potassium bicarbonate.

[0059] In a preferred embodiment, in step (2), the molar ratio of the silicon source to the aluminum source is 5 to 60, the molar ratio of the alkali to the silicon source is 0.005 to 0.5, and the molar ratio of water to the silicon source is 5 to 100, wherein the molar amount of the silicon source is calculated as SiO2, the molar amount of the aluminum source is calculated as Al2O3, and the molar amount of the alkali is calculated as the molar amount of the metal oxide (M2O, M represents an alkali metal).

[0060] For example, in step (2), the molar ratio of the silicon source to the aluminum source is 5, 10, 20, 30, 40, 50 or 60, the molar ratio of the alkali to the silicon source is 0.005, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4 or 0.5, and the molar ratio of the water to the silicon source is 5, 10, 20, 30, 40, 50, 60, 70, 80, 90 or 100, wherein the molar amount of the silicon source is calculated as SiO2, the molar amount of the aluminum source is calculated as Al2O3, and the molar amount of the alkali is calculated as the molar amount of the metal oxide (M2O, M represents an alkali metal).

[0061] In a preferred embodiment, in step (2), based on 100wt% of the mixture, the content of the solid seed crystals is 0.01-50wt%, for example, 0.01wt%, 0.05wt%, 0.1wt%, 0.5wt%, 1wt%, 5wt%, 10wt%, 20wt%, 30wt%, 40wt% or 50wt%, wherein the content of the solid seed crystals is measured based on the SiO2 content therein.

[0062] In a preferred embodiment, the stirring in step (2) is carried out at 60-160°C, preferably 80-150°C, for example 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or 160°C.

[0063] In a preferred embodiment, in step (3), the structure directing agent is selected from one or more of linear or branched alkylamines, cyclic alkylamines, tetraalkylammonium halides, tetraalkylammonium hydroxides, ammonia water, and alkyl diammonium bromides.

[0064] In a further preferred embodiment, in step (3), the structure directing agent is selected from one or more of ethylamine, hexylamine, ethylenediamine, hexyldiamine, tetraethylammonium bromide, tetraethylammonium hydroxide, tetramethylammonium bromide, tetramethylammonium hydroxide, tetrapropylammonium bromide, tetrapropylammonium hydroxide, tetrabutylammonium bromide, tetrabutylammonium hydroxide, ammonia water, hexamethyleneimine, cyclohexylamine, and hexamethylammonium bromide (HMBr2).

[0065] In a preferred embodiment, the molar ratio of the structure directing agent in step (3) to the silicon source in step (2) is 0.0005-1, preferably 0.001-0.5, for example 0.0005, 0.005, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.

[0066] In a preferred embodiment, the structure directing agent is added under pressure in step (3).

[0067] In a further preferred embodiment, the conditions of the pressurized state include: a pressure of 0.3 to 5 MPa, preferably 0.8 to 3 MPa, for example, 0.3 MPa, 0.5 MPa, 1 MPa, 1.5 MPa, 2 MPa, 2.5 MPa, 3 MPa, 3.5 MPa, 4 MPa, 4.5 MPa or 5 MPa.

[0068] Among them, the inventors have found through experiments that adding a structure directing agent in step (3) can obtain a mordenite with a smaller particle size and better application effect than adding a structure directing agent in step (2), and can reduce the amount of the structure directing agent used; compared with the non-pressurized state, the mordenite obtained by adding the structure directing agent under pressurized conditions in step (3) has more excellent performance.

[0069] In a preferred embodiment, in step (3), the crystallization treatment comprises: heating to a crystallization temperature of 120-220° C. and crystallizing at this temperature for 0.5-60 hours.

[0070] For example, the temperature is raised to a crystallization temperature of 120°C, 150°C, 180°C, 200°C or 220°C and crystallized at this temperature for 0.5 hour, 1 hour, 5 hours, 10 hours, 15 hours, 20 hours, 25 hours, 30 hours, 35 hours, 40 hours, 45 hours, 50 hours, 55 hours or 60 hours.

[0071] In a further preferred embodiment, in step (3), the crystallization treatment comprises: heating to a crystallization temperature of 150-200° C. and crystallizing at this temperature for 1-48 hours.

[0072] In a preferred embodiment, in step (4), the post-treatment includes: filtering to obtain a filter cake (for example, using water), washing the filter cake, ion exchange, and heat treatment.

[0073] In a further preferred embodiment, the ion exchange is carried out in a manner commonly used in the art, preferably but not limited to the following limitations: the ion exchange solution is selected from at least one of ammonium nitrate solution, ammonium chloride, hydrochloric acid, sulfuric acid, ammonium sulfate, and ammonium phosphate, the concentration of the solution is 0.01-10 mol / L, the temperature of the ion exchange is 50-120°C, and the time of the ion exchange is 1-20 h; more preferably but not limited to the following limitations: the ion exchange solution is selected from at least one of ammonium nitrate solution, ammonium chloride, hydrochloric acid, sulfuric acid, ammonium sulfate, and ammonium phosphate, the concentration of the solution is 0.05-5 mol / L, the temperature of the ion exchange is 60-100°C, and the time of the ion exchange is 5-15 h.

[0074] For example, the concentration of the solution is 0.01mol / L, 0.05mol / L, 0.1mol / L, 0.2mol / L, 0.4mol / L, 0.6mol / L, 0.8mol / L, 1mol / L, 2mol / L, 4mol / L, 6mol / L, 8mol / L or 10mol / L, the temperature of the ion exchange is 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, and the time of the ion exchange is 1h, 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h or 20h. For example, 90°C, 0.2Mol / L ammonium nitrate solution is used for 8h.

[0075] In a further preferred embodiment, the heat treatment comprises: calcining at 400-700° C. in air atmosphere for 1-10 hours.

[0076] For example, calcination is carried out at 400°C, 450°C, 500°C, 550°C, 600°C, 650°C or 700°C in air atmosphere for 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h; specifically, calcination is carried out at 550°C in air atmosphere for 6 h.

[0077] The third object of the present invention is to provide a zeolite catalyst, which includes mordenite, a binder and a metal component, wherein the mordenite is selected from the mordenite described in the first object of the present invention or the mordenite obtained by the preparation method described in the second object of the present invention.

[0078] In a preferred embodiment, in 100 wt% of the zeolite catalyst, the mordenite accounts for 3-98 wt%, the binder accounts for 1.8-90 wt%, and the metal component accounts for 0.0001-20 wt%.

[0079] For example, in 100wt% of the zeolite catalyst, the mordenite accounts for 3wt%, 5wt%, 10wt%, 20wt%, 40wt%, 60wt%, 80wt% or 98wt%, the binder accounts for 1.8wt%, 2wt%, 5wt%, 10wt%, 20wt%, 40wt%, 60wt%, 80wt% or 90wt%, and the metal component accounts for 0.0001wt%, 0.001wt%, 0.01wt%, 0.1wt%, 1wt%, 5wt%, 10wt%, 15wt% or 20wt%.

[0080] In a preferred embodiment, the binder is selected from at least one of alumina, aluminum sol, silica sol and pseudo-boehmite.

[0081] In a preferred embodiment, the metal component is selected from at least one or more of platinum, molybdenum, bismuth, tin, cadmium, cobalt, nickel, rhenium, palladium, gallium, ruthenium and lanthanum.

[0082] Wherein, the precursor of the metal component is a salt substance of the metal, preferably at least one of nitrate, sulfate and chloride.

[0083] The fourth object of the present invention is to provide a method for preparing a zeolite catalyst, preferably for preparing the zeolite catalyst described in the third object of the present invention, wherein the preparation method comprises: first mixing the mordenite with the binder to obtain a matrix, then loading the metal component thereon, and finally obtaining the zeolite catalyst through post-treatment.

[0084] In a preferred embodiment, the mordenite and the binder are mixed by grinding or pulverizing.

[0085] In a preferred embodiment, the loading adopts any one or more methods of equal volume impregnation method, ion exchange method, precipitation method, grinding method to load the precursor containing metal components on the substrate.

[0086] In a further preferred embodiment, the loading is carried out by grinding and / or equal volume impregnation.

[0087] In a preferred embodiment, the post-treatment includes: first kneading, molding, and drying to obtain a catalyst matrix, and then performing heat treatment to obtain the zeolite catalyst.

[0088] In a further preferred embodiment, the heat treatment comprises: calcining in air atmosphere at 400-700° C. for 1-10 hours.

[0089] For example, the heat treatment includes: calcining at 400° C., 450° C., 500° C., 550° C., 600° C., 650° C. or 700° C. in air atmosphere for 1 h, 2 h, 4 h, 6 h, 8 h or 10 h.

[0090] In a further preferred embodiment, the catalyst is subjected to reduction treatment using a reducing atmosphere, such as a hydrogen atmosphere, in a manner commonly used in the art before use.

[0091] The fifth object of the present invention is to provide the use of the mordenite described in the first object of the present invention, the mordenite obtained by the preparation method described in the second object of the present invention, the zeolite catalyst described in the third object of the present invention, or the zeolite catalyst obtained by the preparation method described in the fourth object of the present invention in the conversion of condensed aromatic hydrocarbons to produce light aromatic hydrocarbons.

[0092] The mordenite and the zeolite catalyst improve the high-efficiency mass transfer performance while mainly solving the problem of low activity and selectivity of the catalyst in the aromatic transalkylation reaction. The catalyst is suitable for processing C9-C14 aromatics to produce xylene, has the characteristics of high activity and good catalyst stability, and can be used in the industrial production of aromatic conversion such as aromatic transalkylation reaction.

[0093] The sixth object of the present invention is to provide a method for converting polycyclic aromatic hydrocarbons into light aromatic hydrocarbons, comprising: reacting polycyclic aromatic hydrocarbons with hydrogen in the presence of the mordenite described in the first object of the present invention, the mordenite obtained by the preparation method described in the second object of the present invention, the zeolite catalyst described in the third object of the present invention, or the zeolite catalyst obtained by the preparation method described in the fourth object of the present invention.

[0094] In a preferred embodiment, the reaction conditions include: a reaction temperature of 300-460°C, and / or a reaction pressure of 2-10 MPa, and / or a hydrogen-to-hydrocarbon molecular ratio of 1.0-3.0 mol / mol, and / or a feed mass space velocity of 0.5-5 h -1 .

[0095] In a preferred embodiment, the condensed ring aromatic hydrocarbons include C9 or higher aromatic hydrocarbons and optional naphthalene series.

[0096] In a further preferred embodiment, based on 100 mol% of the condensed ring aromatic hydrocarbons, the C9 and above aromatic hydrocarbons account for 70 to 100 mol% (e.g., 70 mol%, 80 mol%, 90 mol% or 100 mol%), and the naphthalene series accounts for 0 to 30 mol% (e.g., 0, 10 mol%, 20 mol% or 30 mol%).

[0097] In a further preferred embodiment, based on 100 mol % of the condensed ring aromatic hydrocarbons, the C9 and above aromatic hydrocarbons account for 85 to 95 mol % and the naphthalene series account for 5 to 15 mol %.

[0098] The "total B acid content" and "external surface B acid content" involved in the present invention are obtained by the following method:

[0099] The total acid content was measured using an iS50 Fourier transform infrared spectrometer (Nicolet, USA). 15 mg of the sample was pressed into a self-supporting sheet with a diameter of 11 mm and placed in a vacuum sample cell under vacuum (1×10 -4 The sample was exposed to pyridine vapor at 80°C and adsorbed to saturation, and the sample was degassed to remove physically adsorbed pyridine. The sample was heated at 10°C·min -1 The heating rate was raised to 300°C and the signal was collected. The extinction coefficient was unified as B acid: 1.67 cm·μmol -1 The wave number used is 1540cm -1 The total amount of B acids was calculated based on the signal.

[0100] The amount of acid on the external surface was measured using an iS50 Fourier transform infrared spectrometer (Nicolet, USA). 15 mg of the sample was pressed into a self-supporting sheet with a diameter of 11 mm and placed in a vacuum sample cell under vacuum (1×10 -4 The sample was pretreated with dehydration at 80°C and 2,4,6-trimethylpyridine vapor to achieve adsorption saturation, and the sample was degassed to remove physically adsorbed pyridine. The sample was heated at 10°C·min -1 The heating rate was raised to 300°C and the signal was collected. The extinction coefficient was 8.1 cm·μmol for B acid. -1 , using a wave number at 1540 cm -1 The amount of B acid on the outer surface is calculated based on the signal.

[0101] Example

[0102] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0103] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0104] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.

[0105] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0106] [Examples 1 to 4]

[0107] Pretreatment of synthetic seed crystals. Commercially available molecular sieves were used as seed crystal precursors, treated in NaOH solutions of different concentrations and then dried;

[0108] Zeolite crystallization. Aluminum source, silicon source, alkali source, seed crystal and distilled water are uniformly mixed to obtain a mixture, which is added to a self-generated pressure crystallization kettle and vigorously stirred for a certain period of time; under pressure, a structure directing agent is added, the temperature is raised to the crystallization temperature, and crystallization is carried out at this temperature to complete the crystallization and obtain a crystallized product;

[0109] Post-treatment: After filtering, the solid phase is taken, washed with water, and ion exchange and heat treatment are performed to obtain hydrogen-type molecular sieves Z1-Z4.

[0110] Take 50 grams of Z1, Z2, Z3, and Z4 molecular sieve powder respectively, impregnate a certain amount of ammonium heptamolybdate and nickel nitrate solution (calculated based on the metal Mo loading accounting for 3.5% of the total catalyst mass and the metal nickel loading accounting for 2% of the total catalyst mass), and knead into a mold with 15 grams of alumina, dry at 120 degrees for 4 hours, calcine at 500 degrees for 3 hours, and reduce under hydrogen conditions at 450 degrees for 3 hours to prepare a catalyst.

[0111] 10 g of catalyst was loaded into the fixed bed reactor, and the temperature was raised to 370°C under hydrogen atmosphere. 20 g of reformed C9+ components were passed through the reactor once per hour. The feed mass space velocity was 3.0 h -1 The evaluation was carried out under the conditions of reaction pressure of 3.0 MPa, hydrogen-to-hydrocarbon molecular ratio of 3, and reaction temperature of 370°C. The results are shown in Table 3.

[0112] [Comparative Example 1]

[0113] Take 50 grams of commercially available mordenite, soak it in a certain amount of ammonium heptamolybdate solution (calculated based on the metal loading amount accounting for 3.5% of the total catalyst mass), and knead it with 15 grams of alumina, dry it at 120 degrees for 4 hours, calcine it at 500 degrees for 3 hours, and reduce it under hydrogen conditions at 450 degrees for 3 hours to prepare a catalyst.

[0114] Catalyst evaluation: 10 g of catalyst was loaded into a fixed bed reactor, the temperature was raised to 370°C under a hydrogen atmosphere, and 20 g of reformed C9+ components were passed through the reactor at once per hour. The feed mass space velocity was 3.0 h -1 The evaluation was carried out under the conditions of reaction pressure of 3.0 MPa, hydrogen-to-hydrocarbon molecular ratio of 3, and reaction temperature of 370°C. The results are shown in Table 3.

[0115] [Comparative Example 2]

[0116] The process of Example 1 was repeated, except that the commercially available molecular sieve was not subjected to alkali treatment in step (1).

[0117] [Comparative Example 3]

[0118] The process of Example 1 is repeated, except that the structure directing agent is mixed together with the silicon source, the aluminum source, the base, the water and the solid seed crystal in step (2).

[0119] [Comparative Example 4]

[0120] The process of Example 1 was repeated, except that in step (2), the stirring was performed at room temperature.

[0121] Table 1: Molecular sieve preparation conditions

[0122]

[0123]

[0124] Table 2: Molecular sieve pore structure and acid content distribution

[0125]

[0126] The embodiment of the present invention exhibits a higher mesoporous structure and external specific surface structure, especially the mesoporous pore volume, than the corresponding counterpart. Under the same silicon-aluminum ratio and similar total acid content, the embodiment synthesized in this case exhibits a higher external specific surface acid ratio than the corresponding counterpart, which is beneficial to improve the accessibility of large-sized reactant molecules to acidic sites.

[0127] Table 3: Comparison of catalyst performance

[0128]

[0129]

[0130] By comparison, it can be seen that the embodiment synthesized in the present invention shows a higher conversion rate of heavy aromatics than the corresponding proportion, especially the light conversion rate of naphthalene series, and also promotes the selectivity of xylene in the product, indicating that the ultrafine nano-mordenite synthesized in this example has technical superiority.

[0131] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. A mordenite having an ultra-small particle size, wherein: The mordenite comprises nanoparticles with a diameter of 5 to 100 nm, and the amount of B acid on the outer surface of the mordenite accounts for 5% to 80% of the total B acid amount.

2. The mordenite according to claim 1, characterized in that The mesopore volume of the mordenite is 0.1-0.6 cm 3 / g; preferably, the average mesopore diameter of the mordenite is 5-80nm.

3. The mordenite according to claim 1, characterized in that The specific surface area of ​​the mordenite is 320 to 865 m 2 / g, external specific surface area is 70~610m 2 / g.

4. The mordenite according to any one of claims 1 to 3, characterized in that: The amount of B acid on the outer surface of the mordenite is 30-250 μmol / g.

5. A method for preparing mordenite with ultra-small particle size, preferably used for preparing the mordenite according to any one of claims 1 to 4, the preparation method comprising: (1) treating a seed crystal precursor with alkali to obtain a solid seed crystal; (2) mixing a silicon source, an aluminum source, an alkali, water and the solid seed crystal to obtain a mixture, adding the mixture into a crystallization kettle, and stirring; (3) adding a structure directing agent into the crystallization kettle and performing a crystallization treatment to obtain a crystallized product; (4) The mordenite is obtained through post-treatment.

6. The preparation method according to claim 5, characterized in that: In step (1), the seed crystal precursor and the solid seed crystal are each independently a silicon-aluminum porous material having a MOR and / or FAU and / or BEA and / or MWW and / or FER topological structure; and / or, In step (2), the silicon source is selected from one or more of silicon oxide, water glass, silica sol, ethyl silicate, sodium silicate, silica gel, and white carbon black; and / or, In step (2), the aluminum source is selected from one or more of boehmite, pseudo-boehmite, aluminum hydroxide, sodium aluminate, aluminum sulfate, aluminum nitrate, and aluminum isopropoxide; and / or, The alkali in step (2) is at least one selected from sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, and potassium bicarbonate.

7. The preparation method according to claim 5, characterized in that: In step (2), the molar ratio of the silicon source to the aluminum source is 5 to 60, the molar ratio of the alkali to the silicon source is 0.005 to 0.5, and the molar ratio of the water to the silicon source is 5 to 100, wherein the molar amount of the silicon source is calculated as SiO2, the molar amount of the aluminum source is calculated as Al2O3, and the molar amount of the alkali is calculated as the molar amount of the metal oxide therein; and / or, In step (2), based on 100 wt % of the mixture, the content of the solid seed crystals is 0.01 to 50 wt %.

8. The preparation method according to any one of claims 5 to 7, characterized in that: In step (3), the structure directing agent is selected from one or more of linear or branched alkylamines, cyclic alkylamines, tetraalkylammonium halides, tetraalkylammonium hydroxides, ammonia water, and alkyl diammonium bromides; Preferably, in step (3), the structure directing agent is selected from one or more of ethylamine, hexylamine, ethylenediamine, hexyldiamine, tetraethylammonium bromide, tetraethylammonium hydroxide, tetramethylammonium bromide, tetramethylammonium hydroxide, tetrapropylammonium bromide, tetrapropylammonium hydroxide, tetrabutylammonium bromide, tetrabutylammonium hydroxide, ammonia water, hexamethyleneimine, cyclohexylamine, and hexamethylammonium bromide (HMBr2); More preferably, the molar ratio of the structure directing agent in step (3) to the silicon source in step (2) is 0.0005 to 1, preferably 0.001 to 0.

5.

9. The preparation method according to claim 8, characterized in that: In step (3), the crystallization treatment includes: heating to a crystallization temperature of 120-220° C., and crystallizing at this temperature for 0.5-60 hours; preferably, heating to a crystallization temperature of 150-200° C., and crystallizing at this temperature for 1-48 hours.

10. A zeolite catalyst comprising mordenite, a binder and a metal component, wherein: The mordenite is selected from the mordenite described in any one of claims 1 to 4 or the mordenite obtained by the preparation method described in any one of claims 5 to 9.

11. The zeolite catalyst according to claim 10, characterized in that The binder is selected from at least one of alumina, alumina sol, silica sol and pseudo-boehmite; and / or, The metal component is selected from at least one or more of platinum, molybdenum, bismuth, tin, cadmium, cobalt, nickel, rhenium, palladium, gallium, ruthenium and lanthanum; and / or, In 100 wt% of the zeolite catalyst, the mordenite accounts for 3-98 wt%, the binder accounts for 1.8-90 wt%, and the metal component accounts for 0.0001-20 wt%.

12. A method for preparing a zeolite catalyst, preferably for preparing the zeolite catalyst according to claim 10 or 11, wherein: The preparation method comprises: firstly mixing the mordenite with the binder to obtain a matrix, then loading the metal component thereon, and finally obtaining the zeolite catalyst through post-processing.

13. Use of the mordenite according to any one of claims 1 to 4, the mordenite obtained by the preparation method according to any one of claims 5 to 9, the zeolite catalyst according to any one of claims 10 to 11, or the zeolite catalyst obtained by the preparation method according to claim 12 in the conversion of condensed aromatic hydrocarbons to produce light aromatic hydrocarbons.

14. A method for converting condensed ring aromatics into light aromatics, comprising: In the presence of the mordenite according to any one of claims 1 to 4, the mordenite obtained by the preparation method according to any one of claims 5 to 9, the zeolite catalyst according to any one of claims 10 to 11, or the zeolite catalyst obtained by the preparation method according to claim 12, condensed aromatic hydrocarbons are reacted with hydrogen.

Citation Information

Patent Citations

  • Method for synthesizing mesoporous mordenite

    CN102190316A

  • Preparation method of layered nano-mordenite molecular sieve

    CN102718231A

  • Pillared layered mordenite, and preparation method thereof

    CN106517239A

  • Nano-aggregate sheet-shaped silica zeolite catalyst

    CN107754847B

  • Flaky nano-mordenite molecular sieve synthesis method and mordenite molecular sieve

    CN107963637A